If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5r(r + -7) = 0 Reorder the terms: 5r(-7 + r) = 0 (-7 * 5r + r * 5r) = 0 (-35r + 5r2) = 0 Solving -35r + 5r2 = 0 Solving for variable 'r'. Factor out the Greatest Common Factor (GCF), '5r'. 5r(-7 + r) = 0 Ignore the factor 5.Subproblem 1
Set the factor 'r' equal to zero and attempt to solve: Simplifying r = 0 Solving r = 0 Move all terms containing r to the left, all other terms to the right. Simplifying r = 0Subproblem 2
Set the factor '(-7 + r)' equal to zero and attempt to solve: Simplifying -7 + r = 0 Solving -7 + r = 0 Move all terms containing r to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + r = 0 + 7 Combine like terms: -7 + 7 = 0 0 + r = 0 + 7 r = 0 + 7 Combine like terms: 0 + 7 = 7 r = 7 Simplifying r = 7Solution
r = {0, 7}
| 3t-8=-7t | | 12x+1+10x=133 | | 2*x*y=48 | | 8/2H=8 | | 10-4x=11-x*3 | | 2q=-6q-8 | | 3x^3+37x-84=0 | | 10-4c=11-x*3 | | 2/3=x10 | | 1/7(-14r)= | | 7(v-5)-7=-4(-2v+8)-9v | | =25i^2+20i+25 | | -9+9m=10m-1 | | 59+9x-1=17x+10 | | 5c(5c-6)=0 | | (2x*2y)/2=48 | | -7m+9=29-m | | 600000=x-x/3 | | 98x-6x^2=0 | | 5.5/6=16.5/m | | 10+10d=9d | | -8a+2b=13 | | 39/4=r/12 | | (2x-5y)(3x+2y)= | | 8+3u=4u | | 8+3x=x+111+2x | | 1.3(6y-9)=2y+13 | | (f-7)(6f+7)=0 | | 6z=5z+9 | | 8x-11+2x=120 | | 4x-7=x+2x+3 | | 14x-(25x-18)=34x-(15-30)+18 |